2019
DOI: 10.3389/fimmu.2019.02345
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Peyer's Patches and Microfold Cells in the Gut Immune System: Relevance to Autoimmune Diseases

Abstract: Microfold (M) cells are located in the epithelium covering mucosa-associated lymphoid tissues, such as the Peyer's patches (PPs) of the small intestine. M cells actively transport luminal antigens to the underlying lymphoid follicles to initiate an immune response. The molecular machinery of M-cell differentiation and function has been vigorously investigated over the last decade. Studies have shed light on the role of M cells in the mucosal immune system and have revealed that antigen uptake by M cells contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 127 publications
4
104
1
2
Order By: Relevance
“…At the same time, the issues related to the morphofunctional states of the most representative formations of the immune system of the intestinal mucous membranes, which are Peyer's patches, are underestimated, which, consequently, prompted the present experimental study, involving albino rats. The findings of morphometric analysis showed that after administration of a broad-spectrum antibiotic, Peyer's patches of the small intestine of albino rats remained unchanged both topographically and in their total amount, which contradicts the findings of some authors [8]. But at the same time, their total area is more than doubled, which, according to our data, becomes possible due to the appearance of a new generation of lymphoid nodules in them, the study of which was the aim of the present research.…”
Section: Administration Of An Antibiotic By Any Route Can Cause Dysbacontrasting
confidence: 73%
“…At the same time, the issues related to the morphofunctional states of the most representative formations of the immune system of the intestinal mucous membranes, which are Peyer's patches, are underestimated, which, consequently, prompted the present experimental study, involving albino rats. The findings of morphometric analysis showed that after administration of a broad-spectrum antibiotic, Peyer's patches of the small intestine of albino rats remained unchanged both topographically and in their total amount, which contradicts the findings of some authors [8]. But at the same time, their total area is more than doubled, which, according to our data, becomes possible due to the appearance of a new generation of lymphoid nodules in them, the study of which was the aim of the present research.…”
Section: Administration Of An Antibiotic By Any Route Can Cause Dysbacontrasting
confidence: 73%
“…Active inflammation in CD has been shown in intestinal PP which are even regarded as potential sites of the inflammatory onset [118][119][120]. There is growing evidence that intestinal dysbiosis in connection with an impaired intestinal immune response has a relevance to the development of autoimmune disorders [115]. In line with this assumption, an elevated risk for the onset of CD after gastrointestinal infections has been reported [121].…”
Section: Gp2 As An Autoantigenic Target In Psc-indication Of Microbiamentioning
confidence: 96%
“…Thus, the discovery of GP2 as microbiome-sensing receptor for particularly FimH-positive bacteria on microfold (M) cells of the intestinal follicle-associated epithelium (FAE) fundamentally changed the understanding of GP2's physiological role [113,114]. Peyer's patches (PP) harbouring M cells and located in the epithelium covering MALT of the small intestine play a pivotal role in intestinal immune responses [115]. Along with the Ets transcription factor Spi-B, GP2 is a specific marker of mature M cells characterized by high up-take activity of luminal components [116,117].…”
Section: Gp2 As An Autoantigenic Target In Psc-indication Of Microbiamentioning
confidence: 99%
“…The gut epithelium is composed of enterocytes, and mucus secreting cells (Goblet cells). The ileum and jejunum regions contain Peyer's patches, a gut associated lymphoid tissue where M-cells are located responsible for the uptake of particles (Frey et al 2019, Kobayashi et al 2019. NPs are usually believed to be taken up by Goblet cells and M-cells (Brun et al 2014), although this process is dependent on the particle size (Powell et al 2010).…”
Section: Intestinementioning
confidence: 99%